Resistance to Subterranean clover mottle virus in Medicago truncatula and genetic mapping of a resistance locus - Saqib, M.; Ellwood, Simon; Jones, R.; Jones, M. (CSIRO Publishing, 2009)
Subterranean clover mottle virus (SCMoV), which causes an important disease of annual clover pastures, was inoculated to the annual pasture legume Medicago truncatula, a model legume species used to help understand legume genome structure and function. Two hundred and nine accessions representing the core collection of M. truncatula were inoculated with infective sap containing SCMoV to determine their disease phenotypes. Forty-two of these accessions remained uninfected systemically and so were potentially resistant to the virus. Accession DZA315.16 developed a localised hypersensitive resistance reaction. In an F8 mapping population from a cross between the susceptible parent Jemalong 6/A17 and resistant accession DZA315.16, a total of 166 F8 recombinant inbred lines (RILs) were phenotyped for resistance and susceptibility to SCMoV. Resistant and susceptible lines showed parental phenotypic responses: 84 were susceptible and 82 were resistant, suggesting presence of a single resistance (R) gene. The phenotypic data were combined with genotypic data (76 polymorphic molecular markers) for this RIL population to provide a framework map. Genetic analysis located a single resistance locus termed RSCMoV1 on the long arm of chromosome 6. These results provide a basis for fine mapping the RSCMoV1 gene.